Türkiye'de Ticaret Liselerinin Kuruluş Öyküsü - (:unkn) unknown (My University, 2005)
Ticaret Liselerinin Hamidiye Ticaret Mektebi’nin (Marmara Üniversitesi) kuruluş yılını (1883) ilk kuruluşları olarak benimsemelerinin yanıltıcı olduğu düşünülmektedir. Çünkü, 1883 yılındaki idadi sınıfları, hazırlık sınıflarıdır, diploma vermemektedir ve Hamidiye Ticaret Mektebi’nin bir parçasıdır; ayrı okul niteliği taşımamaktadır. İlk ticaret liselerinin İstanbul’da Ticaret Mekteb-i Ali’sinin ders programlarının ağır olması ve öğrencilerin bu programları izlemede güçlük çekmeleri üzerine Kısm-i Evvel adı ile 1914-15 ders döneminde kurulduğu görülmektedir.

It is supposed to be misleading to assume 1883, the establishment year of Hamidiye Commercial School (Marmara University), as the first emergence of Commercial High Schools. Because the classes established in 1883 were preparation classes and they were part of Hamidiye Commercial School those which do not give a degree. Due to the intensive course schedule at Mekteb-i Ali, the first Commercial High School entitled Kısm-i Evvel was established in 1914-15.
The Establishment Story of Commercial High Schools in Turkey
Keywords: İktisat; Tarih; İşletme